Inovasi Pelayanan Pengaduan Masyarakat Call Center 112 Sebagai Wadah Pengaduan Darurat Di Kabupaten Sidoarjo - Ardhani, Diaz; Wahyudi, Kalvin Edo (Universitas Muhammadiyah Mataram, 2023)
Society will always expect the government to provide quality public services.. Providing access to complaints is one of the efforts to improve public services that can be, so public can submit their complaints regarding the services received. The Government of Sidoarjo Regency is seeking to provide maximum service by launching the Call Center 112 emergency complaint forum, which was launched on June 20, 2022. The purpose of this research is to identify and describe the Call Center 112 public complaint service innovation as an emergency complaint forum in Sidoarjo Regency. The type of research used is qualitative with a descriptive approach. The results of the study show that: 1) Relative Advantage: Call Center 112 Innovation has provided benefits for the community to submit complaints. 2) Compatibility: Call Center 112's innovation complies with regulations, community requirements, and previous complaint forums. 3) Complexity. Call Center 112 is said to be quite complicated in technical reporting and operating procedures. 4) Triability. Call Center 112 has passed the trial stage. 5) Observability: Call Center 112 is easy for OPD to observe, but there is still a lack information on the progress of complaints.